LAYANAN TRANSISI DALAM RANGKA MENYIAPKAN KEMANDIRIAN FINANSIAL SISWA TUNAGRAHITA RINGAN DI SLBC PURNAMA ASIH BANDUNG - Asep Rudi Irawan, - (2018)
Penelitianinibertujuanuntukmendeskripsikanimplementasilayanantransisidalamrangkamenyiapkankemandirianfinansialsiswatunagrahitaringan di SLBC PurnamaAsih, Bandung.Penelitianinimerupakanpenelitiandeskriptifkualitatifdenganpartisipan guru kelas XI, kordinator guru, kepalasekolah, duaorangtuasiswa, danduasiswatunagrahitaringan.Penelitianinibertempat di SLBC PurnamaAsih Bandung yang difokuskanpadasetingkelas XI.Teknikpengumpulan data yang digunakanadalahobservasi, wawancara, dandokumentasi.Data dianalisisdengan proses reduksi, display, danverifikasi data. Hasilpenelitianinimemaparkan lima temabesar, yakni : 1) Kebutuhan ATG di SLBC PurnamaAsih agar dapatmandirisecarafinansial, 2) Layanan yang diberikanuntukmemenuhikebutuhan ATG akanpenentuannasibsendiri, 3) Layanan yang diberikanuntukmemenuhikebutuhan ATG akanakseskeduniakerja, 4) Layanan yang diberikanuntukmemenuhikebutuhan ATG akanpemahamanbersama, 5) Layanan yang diberikanuntukmemenuhikebutuhan ATG akanpengetahuan, kompetensi, danketerampilanuntukbekerja. Pembahasanmengarahpadapotensi, hambatan, dantawaransolusipadasetiaptematersebutdenganberdasarpadateori yang relevan.Penelitianinimenyimpulkanbahwaimplementasilayanantransisi di SLBC PurnamaAsih belum optimal dalammemenuhikebutuhan ATG untukmandirisecarafinansial. Rekomendasiberupaprosedurpelaksanaanmagangdiberikansebagaiupayauntukmengoptimalkanlayanantersebut;---This study aims to describe the implementation of transition services in order to prepare financial independence of mild intellectual disabilties students in SLBC PurnamaAsih, Bandung. This research was a qualitative descriptive study with teacher of class XI, teacher coordinators, principals, two parents of students, and two mild intellectual disabilities (ID) students as participant. This research took place in SLBC PurnamaAsih Bandung which focused on class XI settings. Data collection techniques used observation, interviews, and documentation. Data was analyzed by data reduction, display and verification processes. The results of this study describe five major themes, namely: 1) The needs of ID in SLBC PurnamaAsih to be financially independent, 2) Services provided by school to meet ID's needs of self-determination, 3) Services provided by school to meet ID's needs of access to work place, 4) Services provided by school to meet ID's needs of mutual understanding, 5) Services provided by school to meet ID's need of knowledge, competence and skills to work. The discussion leaded to the potential, obstacles, and solutions offered to each of these themes based on relevant theories. This study concluded that the implementation of transition services in SLBC PurnamaAsih has not been optimal in meeting the needs of ATG to be financially independent. Recommendations in the form of procedures for conducting internships were given as an effort to optimize the service.